Prevalence and associated factors with oral frailty in middle-aged and older hospitalized patients: a cross-sectional study - Dou, Jun-kai; Liu, Huan; Min, Jiahui; Luo, Yang; Liu, Qian; Shi, Xue-zhi; Tao, Xiubin; Zhang, Ming (Frontiers in Public Health, 2025)
BackgroundWith the development of the economy and society, people pay more and more attention to oral health. Oral frailty can limit nutritional intake and make an individual physically weak, which is detrimental to people’s health. Therefore, it is urgent to identify oral frailty and their associated risk factors. In this study, we aimed to evaluate the oral frailty and its influencing factors in Chinese middle-aged and older hospitalized patients.MethodsA cross-sectional study was conducted from May 2023 to February 2024 in 2 tertiary hospitals in Wuhu City, Anhui Province, China. The self-designed sociodemographic information, the Oral Frailty Index-8, the 2-item Connor–Davidson resilience scale (CD-RISC-2), the sarcopenia screening questionnaire, and the three-item short literacy survey were used in this study.ResultsA total of 914 middle-aged and older adults patients were recruited. The prevalence of oral frailty was 48.7% (445/914). In the univariate analysis, oral frailty was significantly associated with age, education, place of residence, monthly income, sarcopenia, resilience, and health literacy. Correlation analysis showed that oral frailty was significantly negatively correlated with sarcopenia, resilience, and health literacy. In the binary logistic regression analysis, oral frailty was significantly associated with sarcopenia, and health literacy. Health literacy was a protective factor of oral frailty.ConclusionThis study aimed to investigate the prevalence of oral frailty and identify the associated influencing factors among middle-aged and older adults patients in Anhui Province, China. This study identified several factors influencing oral frailty in middle-aged and older adults patients. Therefore, the government and relevant departments should implement targeted interventions to improve middle-aged and older adults patients’ oral frailty.